Heavy metals: The main factor limiting the agricultural use of sewage sludge - Val-Moraes, Silvana Pompeia [UNESP]; Moretto, Cristiane [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP] (My University, 2017)
Heavy metals occur naturally in rocks and soils being natural constituents of the Earth's crust that are rarely toxic. The excess heavy metals in soil originate from other sources, which include sewage improper stacking of the industrial solid waste among others. Although sewage sludge is powerful as a fertilizer, rising dry matter yield of many crops, application of many sewage sludge leads to accumulation heavy metals such as arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), mercury (Hg), nickel (Ni), zinc (Zn), and so forth, in the soil. The level of plant uptake, tolerance and bioaccumulation of plants to heavy metals varies among different crops at distinct rates of employment of sewage sludge. Toxic metals and pathogens are risks that are often cited against the use of sewage sludge for nutrient supplementation of soils, and can contaminate the food chain and cut crop yields. The longterm implication of metal availability to plants cultivated in sewage sludge, soil is uncertain, but contamination soil may pose risks and hazards to humans and the ecosystem through direct ingestion or contact with contaminated soil and food chain. The most important factor in charge of movement metals in soil is pH, it is investigated to be the most potent, and rapid method of controlling bioavailability heavy metals in sludge treated soil. With respect to the risk of toxic accumulation of the heavy metals in soil, it is well described due to precipitation in calcareous alkaline soils. Thus, the use of sewage sludge in soil will be right and a potential benefit for sustained agricultural productivity, if applied with adequate guidance to reduce ecological and environmental destruction.